Open partial nephrectomy for high-risk renal masses is associated with renal pseudoaneurysms: assessment of a severe procedure-related complication - Kriegmair, Maximilian; Rathmann, Nils-Andreas; Diehl, Steffen J.; Pfalzgraf, Daniel Philipp; Ritter, Manuel (BioMed research international, 2015)
Objectives. A symptomatic renal pseudoaneurysm (RPA) is a severe complication after open partial nephrectomy (OPN). The aim of our study was to assess incidence and risk factors for RPA formation. Furthermore, we present our management strategy. Patients and Methods. Clinical records of consecutive patients undergoing OPN were assessed for surgical outcome and postoperative complications. Renal masses were risk stratified for tumor complexity according to the PADUA score. Uni- and multivariate analysis for symptomatic RPAs were performed using the -tests and logistic regression. Results. We identified 233 patients treated with OPN. Symptomatic RPAs were observed in 13 (5.6%) patients, on average 14 (4-42) days after surgery. Uni- and multivariate analysis identified tumor complexity to be an independent predictor for symptomatic RPAs (). There was a significant correlation between RPAs and transfusion and the duration of stay ( and ). Symptomatic RPAs were diagnosed with CT scans and successfully treated with arterial embolization. Discussion. Symptomatic RPAs are not uncommon after OPN for high-risk renal masses. A high nephrometry score is a predictor for this severe complication and may enable a risk-stratified followup. RPAs can successfully be located by CT angiography, which enables targeted angiographic treatment.
Gesehen am 30.05.2017